Readiness of health facilities to provide services related to non-communicable diseases in Nepal: evidence from nationally representative Nepal Health Facility Survey 2021 - Achyut Raj Pandey; Deepak Joshi; Santosh Giri; Bikram Adhikari; Bipul Lamichhane; Saugat Pratap KC; Shophika Regmi; Sushil Chandra Baral (BMJ Open, 2023)
Objective To assess the readiness of public and private health facilities (HFs) in delivering services related to non-communicable diseases (NCDs) in Nepal.Methods We analysed data from nationally representative Nepal Health Facility Survey 2021 to determine the readiness of HFs for cardiovascular diseases (CVDs), diabetes mellitus (DM), chronic respiratory diseases (CRDs) and mental health (MH)-related services using Service Availability and Readiness Assessment Manual of the WHO. Readiness score was measured as the average availability of tracer items in per cent, and HFs were considered ‘ready’ for NCDs management if they scored ≥70 (out of 100). We performed weighted univariate and multivariable logistic regression to determine the association of HFs readiness with province, type of HFs, ecological region, quality assurance activities, external supervision, client’s opinion review and frequency of meetings in HFs.Results The overall mean readiness score of HFs offering CRDs, CVDs, DM and MH-related services was 32.6, 38.0, 38.4 and 24.0, respectively. Guidelines and staff training domain had the lowest readiness score, whereas essential equipment and supplies domain had the highest readiness score for each of the NCD-related services. A total of 2.3%, 3.8%, 3.6% and 3.3% HFs were ready to deliver CRDs, CVDs, DM and MH-related services, respectively. HFs managed by local level were less likely to be ready to provide all NCD-related services compared with federal/provincial hospitals. HFs with external supervision were more likely to be ready to provide CRDs and DM-related services and HFs reviewing client’s opinions were more likely to be ready to provide CRDs, CVDs and DM-related services.Conclusion Readiness of the HFs managed by local level to provide CVDs, DM, CRDs and MH-related services was relatively poor compared with federal/provincial hospitals. Prioritisation of policies to reduce the gaps in readiness and capacity strengthening of the local HFs is essential for improving their overall readiness to provide NCD-related services.